2001
DOI: 10.1063/1.1345802
|View full text |Cite
|
Sign up to set email alerts
|

Sharp band edge photoluminescence of high-purity CuInS2 single crystals

Abstract: Temperature-dependent photoluminescence measurements were carried out between 8 and 300 K on CuInS 2 single crystals grown by a traveling heater method. Ten distinct peaks were present in the near-band edge region. Four unknown peaks, observed at 8 K, were found to be due to bound exciton emission. Moreover, the luminescence remained stable up to room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 6 publications
2
65
1
Order By: Relevance
“…Furthermore, some lines related to excitons 1, 2, 4, 5, 6, and 8, that were designated as before [8][9][10], were visible at 4.2 K in PL spectra (depending on the type of single crystal). It is noteworthy that some of these PL lines were previously observed [11][12][13][14]. Experiments on both types of crystals confirmed that lines of free and bound excitons were shifted to high energy as the temperature rose from 4.2 to 78 K. In particular, the line of free A-excitons shifted in this temperature range by 1.8-2.0 meV, which agreed with the literature [8,9,11].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, some lines related to excitons 1, 2, 4, 5, 6, and 8, that were designated as before [8][9][10], were visible at 4.2 K in PL spectra (depending on the type of single crystal). It is noteworthy that some of these PL lines were previously observed [11][12][13][14]. Experiments on both types of crystals confirmed that lines of free and bound excitons were shifted to high energy as the temperature rose from 4.2 to 78 K. In particular, the line of free A-excitons shifted in this temperature range by 1.8-2.0 meV, which agreed with the literature [8,9,11].…”
supporting
confidence: 86%
“…The intensity of the line for free A-excitons was lower than lines for bound excitons for THM single crystals. We were able to resolve in PL spectra the fine structure of free excitons, lines A LPB 1.5347 eV and A UPB 1.5362 eV related to the lower and upper polariton branches of free A-excitons, for the very strong line 2 of bound excitons [8,13,18]. It is known that exciton-photon (polariton) coupling may be characterized by longitudinal-transverse splitting Δ LT A of the A-exciton ground state, the value of which corresponds to the maximum observed spectral separation between the two lines of polariton branches A LPB and A UPB .…”
mentioning
confidence: 99%
“…3), close to that of the chalcopyrite CuInS 2 (1.54 eV) 12 . Indeed, DFT calculations find that a disordered cation sublattice results in a much smaller band gap than that of chalcopyrite CuInS 2 (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…The spectrum shows the main peak of bound exciton (E x6 ) at 1.510 eV with a higherenergy-side tail which is considered to include the peaks of bound excitons (E x4 at 1.516 eV and E x5 at 1.514 eV) and donor-valence band transition (DV at 1.523) referring to the reported data [3,6].…”
Section: Methodsmentioning
confidence: 99%